Revisiting the hallmarks of cancer: The role of hyaluronan. (May 2020) - Caon, Ilaria; Bartolini, Barbara; Parnigoni, Arianna; Caravà, Elena; Moretto, Paola; Viola, Manuela; Karousou, Evgenia; Vigetti, Davide; Passi, Alberto
Abstract: Extracellular matrix (ECM) is a complex network of macromolecules such as proteoglycans (PGs), glycosaminoglycans (GAGs) and fibrous proteins present within all tissues and organs. The main role of ECM is not only to provide an essential mechanical scaffold for the cells but also to mediate crucial biochemical cues that are required for tissue homeostasis. Dysregulations in ECM deposition alter cell microenvironment, triggering the onset or the rapid progression of several diseases, including cancer. Hyaluronan (HA) is a ubiquitous component of ECM considered as one of the main players of cancer initiation and progression. This review discusses how HA participate in and regulate several aspects of tumorigenesis, with particular attention to the hallmarks of cancer proposed by Hanahan and Weinberg such as sustaining of the proliferative signaling, evasion of apoptosis, angiogenesis, activation of invasion and metastases, reprogramming of energy metabolism and evasion of immune response.